GAPS IN SHARK LANDING RECORDS AND TRADE STATISTICS: EVIDENCE FROM OCEAN FISHING PORT NIZAM ZACHMAN - Darmawan; Jane Elizabeth Natalia; Akhmad Solihin; Budhi Hascaryo Iskandar; Fis Purwangka; Zulkarnain; M. Fedi Alfiadi Sondita (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2025)
Shark product traceability is a critical component in supporting sustainable shark fisheries management, particularly to prevent unreported, underreported, or misreported fishing practices. This study analyzes shark landing recording practices at the Nizam Zachman Ocean Fishing Port (PPS Nizam Zachman), Jakarta, one of Indonesia’s main fisheries landing ports. The research was conducted through two weeks of field observations and in-depth interviews with data enumerators, port officers, and fisheries stakeholders. The results indicate that shark landing records still rely on general fish landing standard operating procedures and lack specific guidelines for sharks, particularly for species-level identification and recording of physical condition. Sharks were frequently landed as juveniles, in non-intact conditions, and mixed with other fish species, complicating identification and increasing the risk of data inaccuracy. These conditions may undermine shark product traceability systems and sustainable shark resource management. This study recommends the development of shark-specific landing recording SOPs, capacity building for enumerators through species identification training, and the provision of visual documentation tools to improve data accuracy at landing sites. Key words: shark landing records; shark traceability; unreported fishing